Specification of the Structure of the Electronic Mind: Capabilities and Limitations - Al-Nazil, Kholoud Bint Abdullah Ibrahim (Arts for Linguistic & Literary Studies, 2024)
This study endeavors to elucidate the characteristics of both the simple verb phrase (verb + subject) and the simple nominal sentence (subject + predicate), emphasizing their horizontal, linear, and systematic patterns. It explores methods of expanding sentences to the right, left, and internally, while establishing a standard for prepositions, considering their systems, structure, and connotations. Additionally, there is a brief discussion on describing the relative pronoun to enhance the reader's comprehension and ability to discern sentence quality and structural accuracy. While the immediacy of computer responses may be circumvented, the study aims to achieve a precise equilibrium in modeling systems for artificial intelligence. The study is structured with an introduction and a preface, which outline the study's concepts: description, systems, and artificial intelligence. It further comprises six sections: an analysis of the verb phrase featuring an intransitive verb, an examination of the nominal sentence, an exploration of sentence system connections, a deliberation on systems and structure, a proposal of a model for describing the relative pronoun, and finally an identification of obstacles and potential solutions. The study concludes by asserting that efforts to describe systems for artificial intelligence are feasible, and collaborative endeavors are likely to achieve the desired objectives, with a significant benefit being the alignment with technological advancements. With the information provided, the electronic mind can discern the validity of introduced sentence structures, thereby enhancing its functionality.